Impact of information technology and e-commerce on Indonesia's trade to ASEAN countries - Yulya Aryani; Wina Andari; Suhindarto (Asian Development Bank Institute (ADBI), 2021)
This paper aims to confirm the impact of ICT on Indonesia's trade with ASEAN partner countries and the use of ICT on business activities (e-commerce). The analysis method used in this study is a quantitative analysis of static panel data with a gravity model approach. The study period covers the years 2010 to 2018 and it includes a cross section consisting of nine ASEAN member countries from Indonesia's trading partners. Furthermore, this study uses two groups of variables, namely variables that describe the development and utilization of ICT (IDI and B2B indexes) and variables as indicators of macroeconomic performance (GDP growth, distance, and market size). The results of the analysis show that the IDI and B2B indexes have a significant positive impact in increasing the trade value of Indonesia to trading partner countries in ASEAN. In addition, the economic growth of Indonesia, economic distance, and market size are also proven to have a significant impact on trade between Indonesia and ASEAN countries. Based on the results, the use of ICT can be a key booster for Indonesia's trade performance. Therefore, the development of ICT needs to be a priority agenda for Indonesia's government.
Keywords: F10; O14; O38; 330; ASEAN; e-commerce; gravity model; ICT adoption; trade